Digitalni nekrolozi i 'posthumni' identiteti: Fenomen virtuelnog života nakon smrti / Digital Obituaries and 'Posthumous' Identities: The Phenomenon of Virtual Life After Death (Pregled: časopis za društvena pitanja / Periodical for social issues, 2026)
The phenomenon of digital obituaries and posthumous identities is increasingly shaping the way contemporary society perceives death, remembrance, and the grieving process. Death no longer signifies the complete end of social presence, as digital profiles of the deceased remain active on social media platforms even after physical death, enabling a continuity of symbolic connection with them. This paper explores the emotional, psychological, social, ethical, and legal dimensions of digital memorialization, focusing on the impact of virtual spaces and algorithmic reminders on the grieving process and emotional resolution. A qualitative approach was employed in analyzing secondary sources, grounded in contemporary theories of identity, grief, and digital legacy. The paradoxes of digital mourning are analyzed, wherein memorial profiles and digital obituaries may offer a sense of presence and support, yet simultaneously prolong emotional attachment and hinder acceptance of loss. The paper also examines how the algorithmic functioning of digital platforms generates memories and reminders without sensitivity to the emotional state of users, potentially burdening the grieving process further. It raises critical ethical and legal questions surrounding the management of digital identities after death, including unclear ownership, control, and rights to content removal. The complexity of survivors’ emotional responses and the growing significance of digital legacy further reinforce the need for clear regulations aligned with the psychological dimensions of grief and ethical principles of dignity. In this context, digital memorialization emerges not only as a form of remembrance, but also as a challenge requiring thoughtful consideration within the frameworks of mental health, social practice, and legal accountability.
Keywords: digital obituaries; posthumous identities; virtual mourning; digital memorialization; algorithmic memory; ethical dilemmas of digital inheritance